PERANCANGAN SISTEM PAKAR PENENTUAN USAHATANI BUDIDAYA PADI MENGGUNAKAN METODE CERTAINTY FACTOR BERBASIS ANDROID - Gesa Rizky N; Sri Setyaningsih; Asep Saepulrohman (Ilmu Komputer, FMIPA, Universitas Pakuan, 2019)
Rice is a staple food in several countries of Southeast Asia including Indonesia, rice is the main commodity that acts as the fulfillment of basic needs of carbohydrate and protein. As one of the big rice producer and consumer countries, the increase of rice production is very influential to the state economic condition, effective and efficient national rice production will be achieved if cultivation technology is applied in specific location, in accordance with environmental conditions and farmers. However, the number and ability and extension agents are very limited to serve farmers whose land is diverse. The existence of tools to determine the proper way of cultivating rice-specific locations, easy to use and disseminated will help solve many problems above, The tool used in this study is artificial intelligence is the expert system to help solve the problem due to the limited number of experts or extension workers, many methods used in expert system one of them is certainty factor method which is a method that defines the size of certainty of a fact or rule, to describe the level of expert belief to a problem encountered, by using certainty factor this can level of expert beliefs with android based.